Hyaluronic Acid Binding Sperm Selection for assisted reproduction treatment (HABSelect): study protocol for a multicentre randomised controlled trial. Issue 10 (7th October 2016) - Witt, K D; Beresford, L; Bhattacharya, S; Brian, K; Coomarasamy, A; Hooper, R; Kirkman-Brown, J; Khalaf, Y; Lewis, S E; Pacey, A; Pavitt, S; West, R; et al.
Abstract : Introduction: The selection of a sperm with good genomic integrity is an important consideration for improving intracytoplasmic sperm injection (ICSI) outcome. Current convention selects sperm by vigour and morphology, but preliminary evidence suggests selection based on hyaluronic acid binding may be beneficial. The aim of the Hyaluronic Acid Binding Sperm Selection (HABSelect) trial is to determine the efficacy of hyaluronic acid (HA)-selection of sperm versus conventionally selected sperm prior to ICSI on live birth rate (LBR). The mechanistic aim is to assess whether and how the chromatin state of HA-selected sperm corresponds with clinical outcomes—clinical pregnancy rate (CPR), LBR and pregnancy loss (PL). Methods and analysis: Couples attending UK Centres will be approached, eligibility screening performed and informed consent sought. Randomisation will occur within 24 hours prior to ICSI treatment. Participants will be randomly allocated 1:1 to the intervention arm (physiological intracytoplasmic sperm injection, PICSI) versus the control arm using conventional methods (ICSI). The primary clinical outcome is LBR ≥37 weeks' gestation with the mechanistic study determining LBR's relationship with sperm DNA integrity. Secondary outcomes will determine this for CPR and PL. Only embryologists performing the procedure will be aware of the treatment allocation. Steps will be taken to militate against biases arising from embryologists being non-blinded. Randomisation will use a minimisation algorithm to balance for key prognostic variables. The trial is powered to detect a 5% difference (24–29%: p=0.05) in LBR ≥37 weeks' gestation. Selected residual sperm samples will be tested by one or more assays of DNA integrity. Ethics and dissemination: HABSelect is a UK NIHR-EME funded study (reg no 11/14/34; IRAS REF. 13/YH/0162). The trial was designed in partnership with patient and public involvement to help maximise patient benefits. Trial findings will be reported as per CONSORT guidelines and will be made available in lay language via the trial web site (http://www.habselect.org.uk/ ). Trial registration number: ISRCTN99214271; Pre-results.